2020
DOI: 10.33899/ijvs.2020.126120.1238
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the hbl complex genes in Bacillus cereus isolated from cow raw milk in northwest of Iran

Abstract: Bacillus(B) cereus is regarded as a major foodborne pathogen which is widely distributed in the nature. In addition, it plays an important role in the contamination of ready-to-eat and dairy products. B. cereus causes the two different types of food poisoning in human: the diarrheal and the emetic type. The aim of this study is detection of hbl complex genes in B. cereus isolated from cow raw milk in Northwest of Iran. In the present study, the number of the samples collected from cow raw milk were 120. All th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Following the manufacturer's instructions, the process was carried out. DNA quality was measured spectrophotometrically, and low concentration samples (lower than 100 ng/μL) were eliminated from further analyses (23).…”
Section: Extraction Of Dnamentioning
confidence: 99%
“…Following the manufacturer's instructions, the process was carried out. DNA quality was measured spectrophotometrically, and low concentration samples (lower than 100 ng/μL) were eliminated from further analyses (23).…”
Section: Extraction Of Dnamentioning
confidence: 99%
“…During the processing of dairy product, such procedures are required to reduce bacterial contamination (22). We found that only 12/50 (24%) were diagnosed as S. aureus.…”
Section: Discussionmentioning
confidence: 83%